Character Development Elementary School of Muhammadiyah Jonggol Teachers - Wilarso Wilarso; Awang Surya; Ashari Imamuddin (Program Studi Administrasi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Muhammadiyah Bengkulu, 2022)
As an educational institution, the age of SD Muhammadiyah Jonggol is relatively young and has just entered its sixth year. For this reason, a lot of internal coaching is needed to improve the quality of Human Resources (HR), especially teachers. From the conversation with the Principal of SD Muhammadiyah Jonggol, Imran Fauzan Noor, S.Pd.I, information was obtained that teacher character building is an urgent need. It is necessary to conduct character building for the teachers of SD Muhammadiyah Jonggol. The method used in this Community Service (PkM) activity is the extension method. Activities are carried out face to face. Technical counseling is carried out by delivering the material and then holding several exercises. The result of the activity is an increase in the level of participants' understanding of the material. This is evidenced by several practice cases and answers to the questionnaire